STRATEGI PEMBERDAYAAN KELOMPOK TANI SISTEM HUTAN KERAKYATAN (SHK) LESTARI KAWASAN TAMAN HUTAN RAYA WAN ABDURRAHMAN-HURUN KABUPATEN PESAWANAN LAMPUNG - Herawati, Is Eka (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
The purpose of this research are : (1) to describe the characteristics of the SHK Lestari group in the Wan Abbdurahman-Hurun forest of Pesawanan district, Lampung Province; (2) identifying internal factors (strengths and weaknesses) and external factors (opportunities and threats); (2) to formulate alternative of empowerment strategy of SHK farmer group. The methodology used is the analysis of IFE, EFE and IE matrix which is processed quantitatively and SWOT matrix which is processed qualitatively. The results obtained that the empowerment conducted by SHK Lestari farmer groups can be categorized as an independent group with strong group dynamics, directed to clear group objectives. Empowerment strategies based on IE matrix that farmer groups must run are market penetration, product development, product development, backwand integration, forwand integration and horizontal integration. From the analysis of IFE and EFE factors poured into the SWOT matrix the crucial factor to be considered in the SHK Lestari farmers empowerment strategy is to use the power to exploit the opportunity (S-O) in the highest scoring. Implementation of SHK Lestari farmer empowerment strategy strategy based on IE and SWOT matrix description, the steps to be taken are as follows; 1) Increase the knowledge and skills of more trained farmers to be able to survive and manage agricultural land independently and sustainably, 2) Utilizing NGO assistance, especially in terms of development, training and assistance of SHK Lestari group facilities, 3). Maximize KUB performance and leverage the development of web technologies and transportasi facilities for the development of group farming marketing.